The effects of dietary neutral detergent fiber ratio on the rumen degradability and growth performance of Philippine native goats (Capra hircus Linn.) - Nugroho D; Sevilla CC; Angeles AA; Sunarso . (Jurnal Ilmu Ternak dan Veteriner, 2013)
This research’s objective was to determine the dietary rumen degradability and growth performances of goats fed dietary treatments. Eighteen (18) female goats were grouped into 6 weight classes for the feeding trial experiment, the average BW of the animals that were used was about 7.96 ± 2.21 kg (CV - 27.76%) and were approximately 1 year of age. For the in situ digestibility, three (3) male mature goats surgically fitted with cannulated rumen were used. Three (3) dietary treatments were used for all studies as follows: T1 - 72 : 28  NDF Forage-Concentrate Ratio; T2 - 64 : 36; T3 - 57 : 43. A RCBD was applied for Feeding Trial and a 3 x 3 LSD was used for In Situ Study. Treatments 1, 2 and 3 did not affect the rate of rumen degradability of DM, NDF and CP at 0 hours, potentially degradable fraction (b) and the rate of degradation of b. The treatments affected the intake rate of forage and concentrates on the DM, CP and NDF. However, the total intake of DM, CP and NDF were not affected by the treatments. Growth performance of goats used in this experiment was not affected by the treatments as indicated by the similar production and efficiency. This means that diets given to native goats with ratio of NDF forage of 72.07% can be applied since the value of the output and efficiency of feed utilization had the same value compared to diets ratio of NDF forage of 57.21%. Key Words: NDF Forage, Ration, Goat